Allah und Darwin: Warum die wissenschaftliche Evolutionstheorie die Annahme eines theistischen Gottes doch unplausibler macht - Özbe, Ufuk (2016)

Aufklärung im Islam: Strengt Euch an - Özbe, Ufuk (2016)

„Du Armenier“ (Zum Gedenktag des Genozids an den Armeniern) - Özbe, Ufuk (2015)

Kritik der liberalen Auslegungen des Islam – Die Islamdebatte zwischen politischer Zweckmäßigkeit und intellektueller Redlichkeit - Özbe, Ufuk (2016)

Logical Aliens? Eine Verallgemeinerung und Verteidigung der Psychologismus-Kritik Freges gegen Wittgensteins Naturalismus - Özbe, Ufuk (Zeitschrift für Philosophische Forschung, 2022)
The fundamental laws of logic hold independently of us. Thus, if there were beings who thought in contradiction to these laws, they would be in error. The paper defends this stance of Frege’s against Wittgenstein’s combination of logical constitutivism and logical naturalism. Frege’s arguments against psychologism are more general than his usual wording suggests and are, at their core, directed against the whole of logical naturalism. Contrary to prevailing opinions on this subject, I argue that constitutivism alone cannot deflect Frege’s attack. Rather, constitutivism is neutral to the opposition between logical realism and logical naturalism. The later Wittgenstein was not only a constitutivist, but, as will be explained, also a logical naturalist. By shedding new light on the logical alien problem, I attempt to apply Frege’s generalized arguments to Wittgensteinian naturalism. This naturalism inevitably leads to a radical and self-undermining relativism.
Created from Fastlane, Scopus look-up

Notwendigkeit und Willkürlichkeit der Logik bei Wittgenstein - Özbe, Ufuk (2020)

Was hält einen Begriff im Innersten zusammen? Eine Untersuchung der sokratischen Was-ist-Frage mit Blick auf das wittgensteinsche Konzept der Familienähnlichkeit - Özbe, Ufuk (2019)

Was ist der Unterschied zwischen einem Verrückten und einem Wissenschaftler? Ein Beitrag zur Diskussion zwischen Hans Albert und Norbert Hoerster über das Induktionsproblem im kritischen Rationalismus - Özbe, Ufuk (2015)

Wo, wenn nicht in Europa? Für eine kritische Debattenkultur zum Islam - Özbe, Ufuk (2017)